Application of Capital Asset Pricing Model (CAPM) Sector Company Insurance - Andi Ratna Sari Dewi; Nurdjanah Hamid (Jurnal Manajemen Bisnis, 2023)
Application of Capital Asset Pricing Model in Insurance Sector Companies". For stock selection decisions. In this study, the insurance sector became the author's choice to compare and choose the optimal stock, PT. Maximus Graha Persada Insurance with issuer code (ASMI), PT. Asuransi Harta Aman Pratama with issuer code (AHAP) and PT. Asuransii Multhi Artha Guna with issuer code (AMAG). The method used in this study is a quantitative research method. The sampling technique is generally carried out randomly by collecting quantitative or statistical data The data used in this study is secondary data where the stock price or closing price of the insurance sector is chosen randomly by the author, and the selected one is an insurance company with issuer codes ASMI, AHAP, and AMAG in brackets for five consecutive years. Data analysis techniques used to explain stock investment decision-making use the Capital Asset Pricing Model (CAPM) method. The study results used CAPM that the shares of insurance companies with the issuer code AMAG are the best stocks for investors because they have the lowest positive return rate and beta value.